Well, darling, the difference between x-3 and 3-x is simply the order of subtraction. In x-3, you're subtracting 3 from x, while in 3-x, you're subtracting x from 3. It's like deciding whether you want to take away $3 from your $10 bill or subtract your $10 bill from $3 – either way, you're left with a mess in your wallet.
Chat with our AI personalities
The difference between the expressions x-3 and 3-x lies in the order of subtraction. In the expression x-3, you are subtracting 3 from x, which means you start with x and then subtract 3. In the expression 3-x, you are subtracting x from 3, which means you start with 3 and then subtract x. Therefore, the expressions represent different mathematical operations and may yield different results depending on the value of x.
3x=50
11
That's either the sum or difference of two cubes.
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)
3 - 3x + x2 - x3 = (1 - x)(x2 + 3)